Increased Atrial and Brain Natriuretic Peptides in Adults With Cyanotic Congenital Heart Disease: Enhanced Understanding of the Relationship Between Hypoxia and Natriuretic Peptide Secretion - Hopkins, William E.; Chen, Zengyi; Fukagawa, Naomi K.; Hall, Christian; Knot, Harm J.; LeWinter, Martin M. (Circulation (New York, N.Y.), 2004)
Background— Brain natriuretic peptide (BNP) levels are used in the evaluation of patients with heart disease, yet there is little understanding of the effect of hypoxia on natriuretic peptide secretion. Furthermore, recent data suggest that oxytocin may mediate stretch-induced atrial natriuretic peptide (ANP) secretion. Methods and Results— Ten patients with cyanotic congenital heart defects and 10 control subjects were studied. N-terminal proatrial natriuretic peptide and N-terminal probrain natriuretic peptide levels were 4-fold ( P =0.02) and 12-fold ( P =0.03) greater in cyanotic patients than in control subjects. Cyanotic patients had reduced body water compared with control subjects, although the difference did not reach statistical significance ( P =0.22). In a separate group of patients, cardiac myocytes were isolated from the right atrial appendage during CABG. The amount of oxygen in the buffered saline was varied to simulate hypoxia. Isolated hypoxic atrial myocytes had 43% fewer dense surface secretory granules compared with normoxic myocytes ( P <0.0001). Immunohistochemical staining demonstrated decreased ANP and BNP in hypoxic compared with normoxic right atrial tissue. Isolated myocytes also degranulated when incubated with oxytocin ( P <0.0001), but there was no difference in oxytocin levels in cyanotic patients compared with control subjects ( P =0.49). Conclusions— ANP and BNP are markedly elevated in adults with cyanotic congenital heart disease despite reduced body water. Our results show that hypoxia is a direct stimulus for ANP and BNP secretion in human cardiac myocytes. These findings may have implications for the interpretation of BNP levels in the assessment of patients with heart and lung disease.